EFL University Students’ Performance Assessment in Written Discourse Lexical Collocation - Abdalla, fatima Awadalla (Gezira Journal of Educational Sciences and Humanities; Vol 17 No 2 (2020), 2021)
One of the most important aspects of learning a language, is learning its vocabulary of that language and the appropriate usage. It is not possible to learn a language without its vocabulary. In other words, vocabulary learning lies at the essential in a language learning, and ,therefore, great attention should be paid to issues related to vocabulary learning/teaching. Mastering English Collocations enables EFL learners to be both fluent and accurate. Hence, the current study aimed to assess EFL students’ performance regarding English lexical collocation. The study aimed at discovering which lexical collocations university students practice unsatisfactory and to suggest the most suitable strategies for improving the performance of the students in dealing with lexical collocations in written discourse. The descriptive analytical method was adopted for conducting the study. A diagnostic test and a questionnaire were chosen as tools for data collection. A diagnostic test was given to  seventy two (72) EFL students at the Faculty of Education-Hantoub of  batch 37, semester eight. The questionnaire was distributed to twenty five (25) expert lecturers at the faculties of education universities of Gezira, the Holly Quran and Al-Butana. The Statistical Package for Social Sciences(SPSS) programme was used for data analysis. The study reached the following findings: students’ accurate is unsatisfactory in using English Lexical Collocations (42.3%), mother tongue has negative effect on EFL students (88.5%), generalization is quite clear in students' performance (61.5%). Some EFL students memorize words in isolation which makes the learning so difficult (69%).The study recommends that: it is essential to add more activities and practices regarding English Lexical Collocations, lecturers should make their students aware of English lexical collocations, lecturers need to select the most effective techniques such as contextualization to enhance the performance of students. Syllabus designers should include a considerable number of exercises in student's text books.